Active Soil Pressure of Unsaturated Soil under Rainfall Conditions - Qizhi Hu; Yugang Li (Advances in Civil Engineering)
To study the change in unsaturated active earth pressure under rainfall conditions, based on the thin layer element method and shear strength formula of unsaturated soil, Iverson analysis was used to improve the traditional Coulomb earth pressure theory, and the active earth pressure formula of unsaturated soil considering the change in matric suction was derived under rainfall infiltration conditions. The results show that the active soil pressure of unsaturated soil considering rainfall is greater than that without rainfall. With the continuous occurrence of rainfall infiltration, the active soil pressure of unsaturated soil first increases, then decreases and finally tends to be stable. The above phenomenon is caused by the change in matric suction during rainfall infiltration.